Social Capital as a Catalyst for Community Empowerment: Evidence from KWT Srikandi Mrican, Indonesia - Laila, Aulia Nishful; Sugito (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2025)
This research seeks to investigate the role of social capital in the empowerment of urban agriculture within the Srikandi Women’s Farmers Group (KWT). Employing a qualitative research methodology, the study is conducted at KWT Srikandi located in Mrican, Sleman. The findings reveal that the effective utilization of social capital significantly contributes to the success of the empowerment initiatives within KWT Srikandi. Key values that underpin this process include mutual cooperation, discipline, and responsibility, all of which are reinforced by the awareness and commitment of individual members. Trust is evidenced by the successful delegation of tasks, transparency in program execution, and the solidarity fostered within the group. Social networks are robustly established both internally, among KWT Mrican members, and externally, through collaborations with various partners, including academic institutions, government entities, and the private sector. The advantages of leveraging social capital include the promotion of harmony, enhancement of capacity, and facilitation of successful empowerment outcomes. However, challenges persist, such as limited expansion of partnership outreach and the necessity for improvements in facilities and infrastructure.